2022
DOI: 10.3389/fpubh.2022.963234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile payment on physical health: Evidence from the 2017 China household finance survey

Abstract: Individuals' health status is an essential indicator of the overall strength of a country. Existing literature has studied the determinants of individuals' health, but there is no direct evidence to date on the impact of mobile payment on health. To supplement relevant research and provide insightful policy suggestions to families, government and societies, based on data of 32,058 observations from the 2017 China Household Finance Survey, we estimate the effects of mobile payment on physical health using ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The samples collected from CHFS effectively represent households throughout the entire country. CHFS has been employed in various research topics, including assessing the health payment and the incidence of CHE and MI [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples collected from CHFS effectively represent households throughout the entire country. CHFS has been employed in various research topics, including assessing the health payment and the incidence of CHE and MI [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a study [116] revealed that security and privacy issues are critical aspects in the adoption of IoT technologies, which are considered a main component of smart cities. Another study [117] confirmed that security and privacy are primary issues in the adoption of smart cities. Smart cities rely on IoT devices, sensors, and smart devices, which have weaknesses that can allow an attacker to breach their systems.…”
Section: The Role Of Security Factors In Smart City Adoptionmentioning
confidence: 80%
“…The explanatory variable in this study is mental health. Referring to the study of Zhang et al (2022), this study based on the 8-question CES-D scale in the CFPS to measure individuals' mental health [1]. The 8 questions asked in the CFPS are the frequency of the following feelings or behaviors over the past week 2), ( 3), ( 5), (7), and (8), the responses of a, b, c, and d were assigned as 4, 3, 2, and 1, respectively.…”
Section: Variable De Nition 1 Dependent Variablementioning
confidence: 99%
“…Considering that self-selection may make the estimation results biased and create endogeneity problems. Therefore, this study examines the impact of the household wealth gap on individuals' mental health using propensity score matching, referring to the study by Zhang et al (2022). Speci cally, this study constructs a dummy variable for the level of the wealth gap, which is assigned a value of 1 if the household wealth gap is greater than the mean of all household wealth gap levels and 0 otherwise.…”
Section: Robustness Check (1) Robustness Test I: Replacing the Instru...mentioning
confidence: 99%
See 1 more Smart Citation